2017
DOI: 10.1177/0741932517718359
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Social Dynamics Management: Why the Invisible Hand of the Teacher Matters for Special Education

Abstract: The invisible hand is a metaphor that refers to teachers’ impact on the classroom peer ecology. Although teachers have the capacity to organize the classroom environment and activities in ways that contribute to students’ social experiences, their contributions are often overlooked in research on students’ peer relations and the development of social interventions. To address this, researchers have begun to focus on clarifying strategies to manage classroom social dynamics. The goal of this article is to consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 78 publications
(195 reference statements)
1
63
0
1
Order By: Relevance
“…While many studies have revealed the effect of classroom management on student academic outcomes (e.g., Hattie, 2009), this result supports the finding that student social outcomes are influenced by teachers' classroom management practices as well (e.g., Soodak and McCarthy, 2006). Further, it provides empirical evidence for the concept of the "invisible hand" that refers to the potential teachers have to unobtrusively influence the classroom social dynamics (Farmer et al, 2018). Whether intentionally or not, first to third grade teachers had an impact on the social acceptance level of the peer group through their classroom management practices.…”
Section: Discussionsupporting
confidence: 68%
“…While many studies have revealed the effect of classroom management on student academic outcomes (e.g., Hattie, 2009), this result supports the finding that student social outcomes are influenced by teachers' classroom management practices as well (e.g., Soodak and McCarthy, 2006). Further, it provides empirical evidence for the concept of the "invisible hand" that refers to the potential teachers have to unobtrusively influence the classroom social dynamics (Farmer et al, 2018). Whether intentionally or not, first to third grade teachers had an impact on the social acceptance level of the peer group through their classroom management practices.…”
Section: Discussionsupporting
confidence: 68%
“…Effort should be invested in reducing peer rejection by promoting positive social interactions and train pupils' social skills. Teachers may even seek out suitable playmates and guide social interactions (Farmer et al, 2018). Additionally, teachers can promote acceptance in classrooms by explaining pupils' behavioral difficulties to classmates.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…For example, van den Berg and Stoltz () showed that seating arrangements in the classroom can be a useful tool to increase peer liking. Also, a teacher's general classroom organization and management style can provide opportunities for positive peer relationships, an approach sometimes described as a teacher's ‘invisible hand’ (Farmer, Dawes, Hamm, et al, ). Accordingly, the reduced levels of social interactions between peers in special needs classrooms may be targeted through active observation of peer relationships, followed by systematically providing opportunities for positive peer interactions in class.…”
Section: Discussionmentioning
confidence: 99%